Digital Comic-Supported SQ4R Method: An Innovative Approach to Improving Reading Comprehension Skills in Primary Education - Intan Nur Aini; Nugraheti Sismulyasih SB (Universitas Pendidikan Mandalika, 2026)
This study aims to analyze the effect of the SQ4R (Survey, Question, Read, Reflect, Recite, and Review) method assisted by digital comic media on improving the reading comprehension skills of third-grade students and to describe the improvement of students’ learning activities during the instructional process. This research employed a quantitative approach using a quasi-experimental design with a Nonequivalent Control Group Design. The sample consisted of 25 students in the experimental class and 25 students in the control class. Data were collected through test techniques (pretest and posttest) and non-test techniques in the form of observations of students’ learning activities. Data analysis involved normality and homogeneity tests, the Independent Samples t-test, and N-Gain analysis. The results showed that the SQ4R method assisted by digital comic media had a significant effect on students’ reading comprehension skills, as indicated by the t-value of 2.763, which was higher than the t-table value of 2.011 at the 5% significance level (Sig. = 0.008 < 0.05). The mean posttest score of the experimental class was 80.2, which was higher than that of the control class (72). Furthermore, the N-Gain score in the experimental class was 45.01% (moderate category), while the control class obtained 27.21% (low category). Students’ learning activities in the experimental class reached an average score of 89.38% (very good category), which was higher than that of the control class (56.25%). Therefore, the SQ4R method assisted by digital comic media is effective in improving third-grade students’ reading comprehension skills and learning activities. This method can be considered an alternative instructional strategy for enhancing reading comprehension learning in elementary schools.